Application of soil amendments as a strategy for water holding capacity in sandy soils. Issue 1 (April 2021) - Herawati, A; Mujiyo,; Syamsiyah, J; Baldan, S K; Arifin, I
Abstract: Global warming will affect the pattern of precipitation, evaporation, water run-off, soil moisture, and climate variations so that it can threaten food production. High evaporation and unpredictable precipitation will cause drought. Sandy soils have low water holding capacity, high infiltration, and high runoff. The application of soil amendments able to improve the soil's physical properties through increasing the water holding capacity to increase crop productivity. The research aimed to determine the effect of the application of soil amendments to water holding capacity in sandy soils. The method used was a randomized complete design with one single factor, the type of soil amendments consisting of 7 treatments: P0 (control/without amendment), P1 (cow dung 60 tons ha -1 ), P2 (rice husk biochar 10 tons ha -1 ), P3 (clay-soils 10 tons ha -1 ), P4 (cow dung 60 tons ha -1 + rice husk biochar 10 tons ha -1 ), P5 (cow dung 60 tons ha -1 + clay-soils 10 tons ha -1 ), P6 (rice husk biochar 10 tons ha -1 + clay-soils 10 tons ha -1 ). The results showed that the interaction of rice husk biochar 10 tons ha -1 + clay-soils 10 tons ha -1 significant to increase soil moisture and decrease soil permeability. Combination of cow dung 60 tons ha -1 rice husk biochar 10 tons ha -1 more increase soil aggregate stability index up to 1.87 times than control.